Estudo espectroeletroquímico de politiofenos substituídos para aplicação em dispositivos eletrocrômicos - Luiza De Lazari Ferreira (2015)
This work presents the synthesis and characterization of conjugated polymers (CP) with potential application in electrochromic devices. It has been studied polythiophenes (PT) substituted in the -position and polyaniline (PANI). In the class of -substituted polythiophenes were evaluated properties of two distinct substituent groups: (i) poly(alcoxithiophenes), among these poly(3-methoxythiophene) (PMOT), poly(3,4-ethylenedioxythiophene) (PEDOT) and poly(3,4-dimetoxiothiophene) (PDMOT); and (ii) poly(alkylthiophene), with poly(3-hexylthiophene) (PHT) and poly(3-dodecylthiophene) (PDDT). The synthesis of the polymers was carried out electrochemically, using cyclic voltammetry (CV). After obtaining the polymers, these are characterized by physical-chemistry techniques (infrared spectroscopy FTIR), optical (ultraviolet-visible region absortion (UV-Vis and fluorescence), morphological (SEM scanning electron microscopy) and electrochemical. Electrochromical properties for thin films obtained on ITO were investigated and the potential applications of these materials in electrochromic devices was studied employing the spectrolectrochemical (combining an optical technique and an electrochemical technique). For these films it was possible to know the color variation of the different polymers potential in their electroactivity range, where, going from reduced to the oxidized state, the PMOT and PDMOT´s color variation was from red to blue, in PEDOT was dark blue to light blue, PANI was green to blue, and, finally, PHT and PDDT were from dark blue to black. Among each of the both groups previously mentioned, was chosen one polymer that showed the best electrochromic properties to be used as active layer in electrochromic devices: PMOT and PHT. The PANI was also used, because it presented good electrochromic properties and different color variation, in redox state, from those observed in the polythiophenes. Thus it was possible to apply the RGB (red, green and blue) color matching, obtaining different shades. For the devices construction, films were obtained on flexible substrate ITO/PET (ITO/polyethylene terephthalate), aiming future applicability of this material. Preliminary tests were performed with the built devices to verify their operation. Tests were performed with devices using epoxy adhesive and devices using starch as solid electrolyte, only the first type was observed reversibility of color.